The effect of open-plan workspaces on behavior and performance among Malaysian creative workers - Ahmadpoor Samani, S. (John Wiley and Sons Inc., 2017)
Attracting and retaining creative workers is essential to the success of the companies in Malaysia's Multimedia Super Corridor, a special economic zone and high-tech business district that is an important driver of local development. Guided by a conceptual framework based on environmental comfort theory, researchers surveyed 238 employees in 15 firms in this region to assess the impact of employees’ perceptions of workplace design and conditions on their performance and behavior. The findings show that although open-plan offices can contribute to teamwork and creativity, such distractions as uncontrollable and unwanted noise, lack of visual and acoustical privacy, the presence of others, and other ambient conditions in such settings may reduce not only employees’ satisfaction with their work environment, but also their performance.